Respostas subcelulares a indução de galhas por Baccharopelma dracunculifoliae (Psyllidae) em Baccharis dracunculifolia (Asteraceae) e por Eriogallococcus isaias (Eriococcidae) em Pseudobombax grandiflorum (Malvaceae) - Thiago Alves Magalhaes (2014)
Plant galls have typical tissues originated through cell redifferentiation, hyperplasia, cell hypertrophy, and changes in the patterns of cell division and elongation. These phenomena are important to determine the size and shape of the galls. The variation in the patterns of cell elongation occurs due to changes in the orientation of the microfibrils of cellulose, which is influenced by the acidification of the cell wall. Moreover, pectins and arabinogalactan-proteins (AGPs) influence the cell shape and the tissue morphogenesis. The AGPs may control programmed cell death (PCD). In this work the systems Baccharopelma dracunculifoliae Baccharis dracunculifolia and the system Pseudobombax grandiflorum Eriogallococcus isaias were studied in order to check if the stress generated in the gall tissues could cause changes in the structure of the cell walls in the host plants, if the cytological alterations could lead to programmed cell death and subsequent control of the hypersensitive response (HR), and finally to evaluate the effect of these changes in the generation of the final gall shape. In the first system, the orientation of the cellulose microfibrils, the degree of cell expansion and direction of cell elongation are important on the determination of the final shape of the gall. Both galls present variations in the pectic structure of their cell walls and these variations imply in favorable features to gall development, such as elasticity, extensibility and wall stiffness. The accumulation of ROS in gall tissues affects the structure of the cell wall and chloroplasts, but do not cause MCP, which occurs only during the senescent phase of both galls.